A, The RANCANG BANGUN PENDETEKSI - Marsudi Tangguh Dwi Sasongko; Rini Suwartika (Politeknik Piksi Ganesha Indonesia, 2024)
Abstract : PMI is a humanitarian organization with legal entity status, governed by Law number 1 of 2018 concerning Red Cross activities, aimed at preventing, avoiding, and alleviating the suffering of war prisoners and disaster victims without discrimination of religion, nationality, race, skin color, group, gender, and political views. PMI also has the duty to transform its members into volunteers. This includes Disaster Preparedness and Response Volunteers, First Aid Training for Volunteers, Health Services, Community Welfare Services, and others. In community services, especially first aid services, PMI still requires more first aid equipment to support the performance of volunteers and their services. One such tool is used for emergencies, such as handling sudden cardiac arrest victims. This study developed a prototype heart rate detection device. This heart rate detection prototype is based on ATmega328. The sensor used is a Heartrate Sensor that functions to measure and detect heartbeats. Additionally, an ATmega328 Arduino Pro Mini microcontroller is used to process the incoming signals and display the heart rate per minute on an OLED screen. Based on tests conducted on 10 respondents, this heart rate detection prototype has an average relative error of 0.32% compared to the Elitech Mobile Fox 1 Pulse Oximeter. Keywords : ATmega328, Heart Rate, Heartrate Sensor.